Attending to the importance of context: Trust as a process in global microfinance. Issue 1 (2nd January 2019) - Grimpe, Barbara
ABSTRACT: Previous research has shown that trust is often not a given but grows over time, in a process including various steps of trust-building. In a similar and interrelated vein, the context within which trust emerges is not a given but is continuously processed by the actors involved. The paper explores this understudied research area, namely actors' continuous efforts in shaping the context of (their) trust (in others), and identifies three basic patterns of contextualisation. These are developed from empirical findings from the case of global microfinance. In particular, fund managers' various trust strategies and associated contextualisation practices, which help them to determine the trustworthiness of a potential or already existing investee, are investigated. Against this backdrop, the paper confirms, refines and extends existing process theories of trust and, in particular, existing research into 'active trust'. A key contribution consists of a new concept of active trust, for which the term 'synthesised trustworthiness' is coined.